Enhancement of hydroxyapatite dissolution through structure modification by Krypton ion irradiation. (1st February 2020) - Zhu, Hui; Guo, Dagang; Zang, Hang; Hanaor, Dorian A.H.; Yu, Sen; Schmidt, Franziska; Xu, Kewei
Abstract: Hydroxyapatite (HA) synthesized by a wet chemical route was subjected to heavy ion irradiation, using 4 MeV Krypton ion (Kr 17+ ) with ion fluence ranging from 1 × 10 13 to 1 × 10 15 ions/cm 2 . Glancing incidence X-ray diffraction (GIXRD) results confirmed the phase purity of irradiated HA with a moderate contraction in lattice parameters, and further indicated the irradiation-induced structural disorder, evidenced by broadening of the diffraction peaks. High-resolution transmission electron microscopy (HRTEM) observations indicated that the applied Kr irradiation induced significant damage in the hydroxyapatite lattice. Specifically, cavities were observed with their diameter and density varying with the irradiation fluences, while a radiation-induced crystalline-to-amorphous transition with increasing ion dose was identified. Raman and X-ray photoelectron spectroscopy (XPS) analysis further indicated the presence of irradiation-induced defects. Ion release from pristine and irradiated materials following immersion in Tris (pH 7.4, 37 ℃) buffer showed that dissolution in vitro was enhanced by irradiation, reaching a peak at 0.1dpa. We examined the effects of irradiation on the early stages of the mouse osteoblast-like cells (MC3T3-E) response. A cell counting kit-8 assay (CCK-8 test) was carried out to investigate the cytotoxicity of samples, and viable cells can be observed on the irradiated materials.